KAJIAN GENRE SASTRA DALAM PROSES UPACARA PERNIKAHAN AADAT BATAK TOBA - Reni Vera Wasti; Elmustian Elmustian; Hasnah Faiza AR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study is entitled Study of Literary Genres in the Process of the Toba Batak Customary Marriage Ceremony. In general the problem examined in this study is how the process of the Batak Toba traditional wedding ceremony and literary genre that emerged during the process. This study aims to describe the process and genre of literature that emerged in the Batak Toba traditional ceremony. This research is very useful both theoretically and practically. The operational definition in this study of the literary genre referred to in this study is the type or form of literature in the Batak Toba traditional wedding ceremony in the form of umpasa and umpama or rhymes spoken by certain people, proverbs during the marriage ceremony process from the introduction of young people to the ulaon sadari or wedding reception as well as legends and myths. In the Batak Toba tradition the most important things are umpasa and umpama when at any traditional talk event, especially when in gatherings talk about which leads to the good. This type of research is qualitative research. The data of this research are all literary processes and genres that appear in the ceremony of Batak Toba traditional wedding. The source of this research data was obtained directly from the field or the place of the activity. Data obtained using documentation and interview techniques. From the data obtained in the process of Batak Toba traditional marriage, it was found that the process of Batak Toba traditional marriage which amounted to eleven processes. While the literary genre there are four genres that appear namely umpasa or rhyme, for example or proverbs, legends and myths. Key Words: Study of Literary Genre in the Process of Toba Batak Traditional                     Wedding Ceremon